2006
DOI: 10.1152/ajpheart.00256.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activated neutrophil-mediated sickle red blood cell adhesion to lung vascular endothelium: role of phosphatidylserine-exposed sickle red blood cells

Abstract: . Activated neutrophilmediated sickle red blood cell adhesion to lung vascular endothelium: role of phosphatidylserine-exposed sickle red blood cells. Am J Physiol Heart Circ Physiol 291: H1679 -H1685, 2006. First published May 19, 2006 doi:10.1152/ajpheart.00256.2006.-Activated neutrophils (ANs) increase sickle red blood cell (SRBC) retention/adhesion in the pulmonary circulation. This study investigates the role of neutrophil activation and SRBC retention/adhesion in the pulmonary circulation through a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…The observation that nucleosome and EA levels taken at presentation were highest in patients developing an ACS during admission are nevertheless in line with previous findings suggesting neutrophils to be an important player in the pathogenesis of ACS. 44,45 The observation that neutrophil count does not correlate with EA or nucleosome levels in this study in sickle cell patients is supported by observations from studies in patients with severe sepsis. 40 While EA results reflect haematologica | 2013; 98(11) general PMN activation, it is likely that during vaso-occlusive crisis neutrophil count is a measure for circulating ('countable') neutrophils while it does not reflect neutrophils migrated to tissue or adherent to activated endothelial cells, the latter process being observed in vasoocclusive crisis in mice models for sickle cell disease.…”
Section: Discussionsupporting
confidence: 74%
“…The observation that nucleosome and EA levels taken at presentation were highest in patients developing an ACS during admission are nevertheless in line with previous findings suggesting neutrophils to be an important player in the pathogenesis of ACS. 44,45 The observation that neutrophil count does not correlate with EA or nucleosome levels in this study in sickle cell patients is supported by observations from studies in patients with severe sepsis. 40 While EA results reflect haematologica | 2013; 98(11) general PMN activation, it is likely that during vaso-occlusive crisis neutrophil count is a measure for circulating ('countable') neutrophils while it does not reflect neutrophils migrated to tissue or adherent to activated endothelial cells, the latter process being observed in vasoocclusive crisis in mice models for sickle cell disease.…”
Section: Discussionsupporting
confidence: 74%
“…We have previously reported that activated neutrophils increase SSRBC retention/adherence in the pulmonary circulation (12). We subsequently demonstrated that products released from activated neutrophils increase SSRBC PS exposure and retention/adherence compared with SSRBC controls (13). The increased retention/adherence seen with neutrophil activation was attenuated when lungs were perfused with SSRBCs cloaked with the calcium-dependent phospholipidsbinding protein, annexin V. This mechanistically supports the role of erythrocyte PS exposure in SSRBC adherence to vascular endothelium.…”
supporting
confidence: 58%
“…PSexposed SSRBCs have been demonstrated to be more adhesive to vascular endothelium than non-PS-exposed SSRBCs (13,27,33). In addition, we have recently demonstrated how activated neutrophils increase SSRBC-EC adhesion by further increasing erythrocyte PS exposure above baseline (13).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations